The influence of the work environment and work discipline on the performance of employees of PT. Razer brothers - Aditya Nur Pratama (Indonesia Accounting Research Journal, 2021)
This study aims to determine: (1) The effect of the work environment on the performance of PT. Razer Brothers, (2) The effect of work discipline on the performance of PT. Razer Brothers, (3) The influence of the work environment and work discipline on the performance of PT. Razer Brothers. This research is a causal associative research with a quantitative approach. The sample of this research are employees of PT. Razer Brothers has a total of 130 employees using a population sampling technique. Data collection uses a questionnaire that has been tested for validity and reliability. Data analysis techniques were performed using multiple regression analysis. At a significance level of 5%, the results of the study found that: (1) The work environment has a positive and significant effect on the performance of employees of PT. Razer Brothers, β=0.198* (*p<0.05; p=0.022) with the contribution of the work environment to employee performance of (∆R2) 0.039. (2) Work discipline has a positive and significant effect on the performance of employees of PT. Razer Brothers, β=0.174* (*p<0.05; p=0.045) with the contribution of work discipline to employee performance of (∆R2) 0.030. (3) Work environment and work discipline have a positive effect on the performance of employees of PT. Razer Brothers, which was shown from the results of the regression test that the work environment β=0.198* (*p<0.05; p=0.021) and work discipline β=0.174* (*p<0.05; p=0.042). Contribution of work environment and work discipline to explain the performance of employees of PT. Razer Brothers by (∆R2) 0.069*.